The theory of the numerical-analytic method: Achievements and new trends of development. VII - Ronto, M. I.; Samoilenko, A. M.; Trofimchuk, S. I. (Ukrains’kyi Matematychnyi Zhurnal, 1999)
For the numerical-analytic method suggested by A. M. Samoilenko in 1965, we analyze the application to abstract differential equations, implicit equations, and control problems.